FORMATION OF THE EDUCATION SYSTEM IN THE CONTEXT OF THE PHILOSOPHICAL IDEAS OF THE ENLIGHTENMENT - Кравченко, А. А. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The problem of the educational system evolution is inseparable from Enlightenment, which determined the development of European science and knowledge in classical and non classical stages of the development of society.